2018
DOI: 10.3389/fimmu.2018.01184
|View full text |Cite
|
Sign up to set email alerts
|

The Calcineurin Inhibitor Tacrolimus Specifically Suppresses Human T Follicular Helper Cells

Abstract: BackgroundT follicular helper (Tfh) cells are key players in the production of antibody-producing B cells via the germinal center reaction. Therapeutic strategies targeting Tfh cells are important where antibody formation is implicated in disease, such as transplant rejection and autoimmune diseases. We investigated the impact of the immunosuppressive agent tacrolimus on human Tfh cell differentiation and function in transplant recipients.MethodsPaired blood and lymph node (LN) samples were obtained from 61 tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
52
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 53 publications
4
52
1
Order By: Relevance
“…Among our study participants, there were 5 patients who had chronic GVHD and were receiving immunosuppressive drugs such as prednisolone, tacrolimus, cyclosporine, and mycophenolate mofetil; 4 patients did not recover their B cell count after rituximab infusion, and the remaining 1 patient recovered after the discontinuation of immunosuppressive drugs. These drugs are known to have side effects that inhibit B cell proliferation . Although the reason for B cell inhibition is unclear, we suggest that delayed B cell recovery was caused by the immunosuppressive drugs, and not by rituximab administration.…”
Section: Discussionmentioning
confidence: 74%
“…Among our study participants, there were 5 patients who had chronic GVHD and were receiving immunosuppressive drugs such as prednisolone, tacrolimus, cyclosporine, and mycophenolate mofetil; 4 patients did not recover their B cell count after rituximab infusion, and the remaining 1 patient recovered after the discontinuation of immunosuppressive drugs. These drugs are known to have side effects that inhibit B cell proliferation . Although the reason for B cell inhibition is unclear, we suggest that delayed B cell recovery was caused by the immunosuppressive drugs, and not by rituximab administration.…”
Section: Discussionmentioning
confidence: 74%
“…20 The reasons of the occurrence of early primary immunization in solid organ transplantation are unclear. In the context of therapy with calcineurin inhibitors (cyclosporine and tacrolimus) known to target T follicular helper cells, 21 we hypothesize that B cells activated by RBC epitopes do not enter germinal centers and instead are committed to the extrafollicular pathway of B cell growth which produce short-lived antibody response as early as 7-8 days after immunization but fail to generate long-lived memory B cells. 22 For these reasons, to avoid the underestimation of alloimmunization frequency, we included all anti-D responses detected at least 10 days after D + PC transfusion.…”
Section: Discussionmentioning
confidence: 99%
“…Although a few studies have reported a negative effect of tacrolimus on tDC maturation, others have demonstrated a positive role for tacrolimus in inducing the maturation of imDC to tDC cells, . B cells (activities, antibody production, and class switching) are suppressed via T follicular helper cells . These findings suggest that tacrolimus can inhibit rejection of and induce tolerance to the fetus by inhibiting activated NK/NKT cells and macrophages, and may also induce the differentiation of imDC to tDC.…”
Section: Site Of Tacrolimus Actionmentioning
confidence: 98%
“…Elucidation of the detailed mechanisms of signal transduction in cells has led to the successful use of tacrolimus in the fields of transplantation andautoimmune disease . Tacrolimus has been reported to act not only via the CN‐NFAT pathway in T cells, but also in other cell types, including NK/NKT cells, macrophages, B cells, and DC cells . Direct inhibition occurs in T cells, NK/NKT cells, and macrophages.…”
Section: Site Of Tacrolimus Actionmentioning
confidence: 99%
See 1 more Smart Citation